Congenital Chylothorax in a Late Preterm Infant and Successful Treatment With Octreotide - Ning-Hui Foo; Yea-Shwu Hwang; Chin-Chuan Lin; Wen-Hui Tsai (Elsevier, 2011)
Chylothorax is defined as abnormal accumulation of lymphatic fluid in the pleural space and is a rare condition in neonates. Chylothorax causes respiratory and nutritional problems and a significant mortality rate. Octreotide is a long-acting somatostatin analog that can reduce lymphatic fluid production and has been used as a new strategy in the treatment of chylothorax. Here, we report a premature baby with severe bilateral pleural effusion diagnosed by prenatal ultrasound and subsequently confirmed to be congenital chylothorax after birth. This newborn baby was initially treated with bilateral chest tube insertion to relieve severe respiratory distress. However, the chylothorax recurred after a medium-chain-triglyceride-enriched formula was initiated. The accumulation of chylothorax diminished after the administration of octreotide. Therefore, octreotide may allow the patient to avoid invasive procedures, such as reinsertion of chest tubes or surgery.